Design of Control and Monitoring System for Remote Television Transmitter Stations Based on Internet of Things (Case Study on ITV Malang) - Wincoko Wincoko (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2022)
The Problem with television stations between the Master Control Room (MCR) studio and TV Transmitters is that the location difference is quite far, so there are problems in controlling the transmitter station. Required special personnel assigned to the transmitting station. The obstacle that is often faced by MCR is the difficulty in monitoring between the transmitter and the controller studio. Therefore, it is necessary to control and control the Internet of Things (IoT) based centralized. The method used in making this system is waterfall. The system in this case study also has several features or functions that facilitate the management and control of television transmitters, namely in the form of monitoring the temperature of the transmitter engine, adjusting the on and off lights, turning on the air conditioner, turning the TV transmitter on and off. The results showed that all of these systems were connected to the internet through the website as a control and monitor medium, so that the Master Control Room (MCR) section could determine the condition of the TV transmitter.